Efektivitas Pemberian Dana Usaha Terhadap Pemberdayaan Ekonomi Perempuan (Studi Kasus Koperasi Wanita Mayangsari 38b Banjarrejo) (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2023)
One of the activities to encourage women's empowerment in the economic sector is the provision of business financing through non-bank financial institutions such as banks and cooperatives. Working capital loans are goods (money) or services used to run a business that must be repaid within a certain period of time based on a contract between the borrower and the lender. This study explores how business financing from non-bank institutions, like the Mayangsari Women's Cooperative, empowers women in the economic sector. The type of research used is field research. Field research is research carried out in the field or at the research site, namely the Mayangsari 38B Banjarejo Women's Cooperative. Borrowers met key criteria, including generating income and developing their businesses. The success lies in adhering to empowerment principles. Members understand the loan purpose and strive for effectiveness metrics. The program aims to start or grow businesses, ensure good loan repayment, offer income opportunities, and foster independent business ownership. This is evident in members acquiring new skills and some even starting new businesses without further loans, proving the program's sustainability. This case study showcases the potential of business loans to empower women, not only financially but also by fostering independence and entrepreneurial spirit. By adhering to sound principles, such programs can contribute significantly to women's economic development and overall well-being.
Keywords: Providing Business Capital Loans; Women's Empowerment; Business Financing